PERANCANGAN UI/UX APLIKASI REKAPIN SEBAGAI MARKETPLACE JASA AKUNTANSI MENGGUNAKAN METODE DESIGN THINKING - Ridan Gumilar; Giri Adhi Wijaya; Anisa Risqina Setia Putri; Genta Nazwar Tarempa (STMIK Catur Sakti Kendari, 2026)
UMKM, as a pillar of the Indonesian economy, still face limited access to affordable professional accounting services. This study designed a UI/UX prototype for the Rekapin app, a fintech-based marketplace platform that digitally connects UMKM operators with accounting service providers. The design utilized the Design Thinking method through five iterative stages based on user needs. Key features developed include KYC verification, an escrow mechanism via the RekapPay e-wallet, an electronic e-NDA contract, a virtual workspace, and a dispute arbitration system. Usability testing using the System Usability Scale (SUS) yielded an average score of 71.75, placing Rekapin in the “Good” category, grade B, and “Acceptable” status. These results demonstrate that the Design Thinking method effectively produces a functional and user-friendly interface, positioning Rekapin as a significant fintech solution for UMKM financial management in Indonesia.